Comparison of physical and technical performance in European soccer match-play: FA Premier League and La Liga - Dellal, A.; Chamari, K.; Del Wong, P.; Ahmaidi, S.; Keller, D.; Barros, R.; Bisciotti, G. N.; Carling, C. (European Journal of Sport Science, 2011)
The aim of this study was to compare match performance in professional soccer players across two major European championships: Spanish La Liga and English FA Premier League (FAPL). Data were collected using a computerized match analysis system. A total of 5938 analyses were recorded during the 2006-2007 season. The players were classified into six positional roles: central defenders, full backs, central defensive midfielders, wide midfielders, central attacking midfielders, and forwards. The match performance variables analysed included: (i) physical activity - total distance covered, distances covered at high-intensities both with and without possession of the ball; (ii) technical actions - heading and ground duels, passing, time in possession, and ball touches. Comparison of the total distance covered by FAPL and La Liga players showed no difference across individual playing positions but FAPL players generally covered greater distances in sprinting. In contrast, more of the total distance in sprinting was covered by La Liga players when their team was in possession (values from P < 0.05 to P < 0.001), while an equal total sprint distance, irrespective of possession, was observed in FAPL players. La Liga players won more heading duels (49.32% vs. 48.68%) and performed the same proportion of successful passes (76.17%). FAPL wide midfielders had ~20% more ball touches per possession than their La Liga counterparts (2.24±0.54 vs. 2.03±0.55, P < 0.001). In conclusion, our results show that FAPL and La Liga teams present differences in various physical and technical aspects of match-play, suggesting that cultural differences may exist across professional soccer leagues and playing positions.